2005
DOI: 10.1111/j.1523-1755.2005.00739.x
|View full text |Cite
|
Sign up to set email alerts
|

Fibrate prevents cisplatin-induced proximal tubule cell death

Abstract: Bezafibrate treatment inhibits cisplatin-mediated tubular injury by preventing the activation of various cellular mechanisms that lead to proximal tubule cell death. These findings support our previous observations where the use of fibrates represents a novel strategy to ameliorate proximal tubule cell death in cisplatin-induced acute renal failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
85
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(100 citation statements)
references
References 43 publications
13
85
1
1
Order By: Relevance
“…We did not examine this possibility here because (i) while Bcl-2 is abundant in embryonic kidney and is expressed in correlation with the apoptosis-related remodeling processes typical of this developmental stage, its expression in adult renal cells is low (63); and (ii) our attempts to detect Bcl-2 in the strain of LLC-PK 1 cells used here revealed only minimal expression by Western blotting (12) or RT-PCR analysis (H. Servais, unpublished data). Yet, others have clearly observed such an expression in LLC-PK 1 cells and have demonstrated its role in protecting the cell from apoptosis in at least two situations of drug-induced nephropathy (46,74). The literature, however, suggests that rather than Bcl-2, it is its homologue, Bcl-xL, that may be controlling apoptosis in renal cells (37,49).…”
Section: Discussionmentioning
confidence: 96%
“…We did not examine this possibility here because (i) while Bcl-2 is abundant in embryonic kidney and is expressed in correlation with the apoptosis-related remodeling processes typical of this developmental stage, its expression in adult renal cells is low (63); and (ii) our attempts to detect Bcl-2 in the strain of LLC-PK 1 cells used here revealed only minimal expression by Western blotting (12) or RT-PCR analysis (H. Servais, unpublished data). Yet, others have clearly observed such an expression in LLC-PK 1 cells and have demonstrated its role in protecting the cell from apoptosis in at least two situations of drug-induced nephropathy (46,74). The literature, however, suggests that rather than Bcl-2, it is its homologue, Bcl-xL, that may be controlling apoptosis in renal cells (37,49).…”
Section: Discussionmentioning
confidence: 96%
“…By contrast, cisplatin treated PPARα null mice fail to demonstrate a protective effect of fibrate treatment and do not reverse cisplatin-mediated inhibition of MCAD (46). In our most recent study done in renal epithelial cells in culture, we found that cisplatin directly inhibited PPARα activity in these cells, and this event was accompanied by increased accumulation of NEFA (57). Pretreatment with fibrate prevented the inhibition of PPARα activity, and the accumulation of NEFA, and also prevented cisplatin-induced proximal tubule cell death, supporting our in vivo observations about the protective role of PPARα ligands in reducing accumulation of NEFA and preventing cisplatin-mediated nephrotoxicity.…”
Section: Cisplatin-mediated Renal Lipid Accumulation Is Ameliorated Bmentioning
confidence: 92%
“…Inhibiting these cisplatin mechanisms leads to some renoprotection, suggesting a combination of strategies is necessary. A previous study reported bezafibrate, a member of fibrate drug family, effectively protected against cisplatin nephrotoxicity (Nagothu et al, 2005). Therefore, this notion prompts investigation of other FDA-approved fibrate drugs like fenofibrate and clofibrate.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis induced by cisplatin was suppressed by bezafibrate via prevention of proapoptotic Bax translocation from the cytosol to the mitochondrial fraction and increased expression of antiapoptotic molecule Bcl-2 (Nagothu et al, 2005), suggesting fibrates may be a novel strategy to ameliorate proximal tubule cell death in cisplatin-induced acute renal failure. Since cisplatin-induced nephrotoxicity is mediated by several mechanisms such as induction of ROS and activation of MAPK pathways, it is possible that benzafibrate's protective effect involves these signaling pathways.…”
Section: Introductionmentioning
confidence: 99%